The generational cohort effect in the context of responsible consumption. Issue 5 (13th May 2019) - Ivanova, Olga; Flores-Zamora, Javier; Khelladi, Insaf; Ivanaj, Silvester
Abstract : Purpose: The purpose of this paper is to identify the generational cohort effect on responsible consumer behavior. Based on the theory of planned behavior and the generational cohort theory, the authors test the impact of perceived consumer effectiveness (PCE), media exposure (ME), the social group influence of family and peers and self-identity on the intention of Generation X and Generation Y to purchase environmentally responsible products. Design/methodology/approach: The data were collected from 1, 870 respondents in France. Based on the factor scores from a confirmatory factor analysis, the authors tested for interaction effects by employing regression and path analyses. A two-group structural model evaluated the strength of each cohort's direct effects and the significant differences between the groups. Findings: The results reveal a generational (cohort) effect on the relationship between PCE and ME and the intention to purchase environmentally responsible products. Research limitations/implications: The convenience sample shows bias toward younger people, especially students. In addition, some latent variables show low AVE scores, probably due to scale interpretation differences. By measuring purchase intention, the study disregards the actual behavior of consumers. Practical implications: To increase consumers' personal involvement in responsible purchasing behaviors, marketers could cater to the social desirability side of Gen Y by emphasizing products that express community values; on the other hand, marketers could appeal to the PCE of Gen X by providing more information and convincing them that their actions matter. Social implications: The efficiency of awareness and promotional campaigns for environmentally responsible products will be enhanced when marketers employ segmentation based on generational cohorts. Originality/value: The study contributes to a better understanding of responsible consumer behavior by identifying generational cohort differences.